Redesign Workstation Based on Anthropometry to Reduce Packing Delay and Improve Production Performance - Misbach Munir; M. Imron Mas'ud; Subchan Asy'ari (JTI: Jurnal Teknik Industri, 2026)
This study aims to redesign the workstation in the filling-packing process based on anthropometric data to reduce packing delay and improve production performance. Previous workstation redesign studies have predominantly focused on operator comfort and ergonomic considerations, while the integration of anthropometric design with work activity analysis and production performance, particularly in addressing human–machine imbalance in filling-packing operations, remains limited. The study employed a quantitative ergonomic approach involving 30 operators, with data collected through direct observation, interviews, anthropometric measurements, work activity analysis, and packing time measurement. Anthropometric data were analyzed to determine workstation dimensions, while the existing and redesigned work sequences were compared to identify inefficient activities and evaluate improvements in production performance. The redesign used the 50th percentile anthropometric dimensions as the primary design basis, resulting in a conveyor height of 102 cm, worktable height of 80 cm, worktable length of 73 cm, and worktable width of 144 cm. The redesigned workstation reduced the packing time per carton from 24.0 seconds to 11.2 seconds, representing a 53.3% reduction. The redesigned work sequence also reduced unnecessary movements and waiting activities, thereby improving workflow and reducing product accumulation at the conveyor end. These findings demonstrate that anthropometry-based workstation redesign, combined with work activity improvement, can contribute to reducing packing delays and improving production performance by supporting a more balanced interaction between operator capability and machine output.